Adaptive control method for drilling robot based on coal and rock drillability - LI Wangnian; ZHANG Youzhen; TIAN Hongliang; LI Quanxin; WEI Hongchao (Gong-kuang zidonghua, 2023)
Due to the complex geological and mechanical environment of coal-bearing strata, the feed resistance of the drilling rig feed system and the load torque of the rotary system are complex and diverse. The existing technology only controls the actuator through established procedures for procedural actions. The adaptive intelligent control level of the drilling process is low. When the drilling conditions change, it is easy to cause accidents such as sticking and breaking. It reduces the drilling efficiency of the drilling robot and affects the work cycle. To solve this problem, a dual loop PID adaptive control method for feed and rotation of drilling robots based on coal rock drillability is proposed. Firstly, with drilling efficiency and drilling safety as control objectives, drilling pressure and torque are selected as input parameters of the coal rock drillability model. Wavelet packet decomposition is used to extract features of drilling process data to obtain sample data and test set. BP neural network is used for training and verification to establish coal rock drillability model and obtain recommended drilling speed and rotation speed under current drilling conditions. Secondly, based on the coal rock drillability model, a constant torque control strategy and a constant drilling speed control strategy based on PID control are designed. The drilling robot feed rotation control system adjusts the set drilling pressure through a constant torque control circuit to achieve constant torque control. The system adjusts the set torque through a constant drilling speed control circuit to achieve constant drilling speed control, improving drilling efficiency while ensuring its safe operation. Finally, A drill-rock interaction model reflecting the feed swing load is developed. The simulation testing is conducted on the dual loop PID adaptive control method for the feed rotation of the drilling robot. The results show the following points. ① When the hardness of coal and rock remains unchanged, this control method can achieve constant torque and constant drilling speed control, with torque maintained at 2 000 N·m and drilling speed maintained at 6 mm/s. ② At 50 seconds, by increasing the hardness of coal and rock and adopting an adaptive adjustment strategy, the drilling robot can quickly reach a stable state in terms of drilling pressure, rotation speed for the rotary control system. ③ If the recommended drilling speed of 6 mm/s corresponds to an actual torque of 2 350 N·m which exceeds the permissible load torque for the operation of the drilling robot and the actual speed of 85 r/min is less than 95% of the recommended speed, the recommended drilling speed setting is reduced by means of the drilling speed trim module. The drilling pressure is adjusted to adjust the drilling robot's torque to the optimal torque, ensuring that the drilling robot is stable again in the constant torque and constant drilling speed control state.